The Value of Classical Islamic Thought for Muslims Today (American Journal of Islam and Society, 2020)
This article challenges the assertion, found in the writings Dr. Taha Jabir Al-Alwani and other Muslim reformers, that Islamic thought declined precipitously in the early centuries of Islam and is of little value to contemporary Muslims.  It introduces readers to the sophisticated thought of four diverse Muslim thinkers from the 5th/11th century who each wrote about topics that remain important to Muslims today, such as the nature of the soul, ethics, the purpose of knowledge, and spirituality.  These thinkers are the philosopher-historian Miskawayh, the Sunni Mu'tazili al-Hakim al-Jishumi, the Zahiri Ibn Hazm, and the Hadith scholar al-Khatib al-Baghdadi.  In addition to drawing specific lessons from these classical thinkers’ writings, the article encourages contemporary Muslims to emulate their practice of reading widely, including works of Muslim philosophy and theology, and to appreciate the significant connection they made between the acquisition of knowledge and its application to daily life.  Download